Penanaman Nilai-Nilai Keagamaan dan Moral Siswa Melalui Penerapan Pembelajaran Biologi Berbasis Al- Qur’an di MTs dan MA ‘PUI’ Maja Kabupaten Majalengka - Yeni Suryaningsih; Najma Syaidatul Fathiyah (SANISKALA : Jurnal Pengabdian Masyarakat, 2026)
This community service is carried out as an effort to instill religious and moral values ​​in students through the implementation of Al-Qur'an-based biology learning carried out together with teachers and students in the MTS and MA 'PUI Maja environment, Majalengka Regency. As an effort to instill religious and moral values ​​in students, it can be done with various approaches, strategies and methods that are expected that students will not only master the material but also be able to form behaviors that are in accordance with religious values ​​and in line with the goals of national education which aims to form people who are faithful and pious and have noble character, not only developing the potential of cognitive intelligence alone. The purpose of this community service activity is to instill religious and moral values ​​in students through the implementation of Al-Qur'an-based biology learning. This community service activity begins with recording and analyzing Al-Qur'anic verses that are in accordance with biology material both implicitly and explicitly. Furthermore, the activity implements the integration of biology learning with Al-Qur'anic verses using methods through stages, namely observation and needs analysis, initial socialization, training and counseling, and partner mentoring. The result of this service is that through this service, students can instill values ​​and morals by developing learning of biological materials integrated with verses of the Qur'an, including living things, microorganisms, food processes, genetics, brain structure, ecology, reproduction and embryology.